DAMPING PROPERTY ANALYSIS OF ELECTROMAGNETIC SHOСК ABSORBER WITH MECHANICAL MOTION RECTIFIER - FAN ShengPing; LI Jing; LI LinYong; FAN XiaoPeng; LI HuaLiang; GAO NanSha (Jixie qiangdu)
In order to determine the damping characteristics of the electromagnetic shock absorber under different working conditions, the theoretical modeling and test of the electromagnetic shock absorber with mechanical rectification device were carried out. Firstly, the dynamie transmission model and electromechanical coupling model of electromagnetic shock absorber were built theoretically, and its dynamics and electrics characteristics are analyzed. Secondly, a test bench of electromagnetic shock absorber is built from the engineering point of view, and the experimental study of its damping characteristies under different working conditions was carried out. Finally, the theoretical simulation results were compared with the test results. The results show that theoretical results and test results have the same variation trend. The equivalent damping coefficient of electromagnetic shock absorber will decrease from 1 208 N・s/m to 496 N・s/m when the load resistance increases from 5 Ω to 100 Ω. In addition, the results of decrease of equivalent damping coefficient from 874 N・s/m to 660 N・s/m when the increase of excitation frequency from 0.5 Hz to 2 Hz or the increase of excitation amplitude from 20 mm to 40 mm.